PENGARUH PSYCHOLOGICAL EMPOWERMENT, EMOTIONAL INTELLIGENCE DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KNOWLEDGE SHARING PADA SEKOLAH BINA BANGSA BANDUNG [THE EFFECT OF PSYCHOLOGICAL EMPOWERMENT, EMOTIONAL INTELLIGENCE, AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR ON KNOWLEDGE SHARING IN BANGSA SCHOOL BANDUNG] - Jesica Trifenanto (Jurnal Ketopong Pendidikan, 2021)
This study aims to determine the effect of psychological empowerment, emotional intelligence, and organizational citizenship behavior on knowledge sharing in educators and education staff at Bina Bangsa School Bandung. The data in this study were obtained from the distribution of questionnaires given to 64 educators and education staff in the school. Further research data were analysed using SEM analysis with Partial Least Square (PLS) technique. The research itself uses a quantitative approach with the path analysis method to find out the coefficient effect of each of the variables. In order to collect the data with the census method using a questionnaire. The issue from the research stated that psychological empowerment, emotional intelligence, and organizational citizenship behavior have a positive effect on knowledge sharing in Bina Bangsa School. Furthermore, psychological empowerment and emotional intelligence have a positive effect on knowledge sharing through organizational citizenship behavior.